Pengaruh Independensi, Etika Auditor, Kompetensi, dan Standar Audit Terhadap Kualitas Audit (Studi Empiris Pada KAP Jawa Tengah dan Yogyakarta) - Triana, Anggi Cahyaning; , Drs. Eko Sugiyanto, M.Si (2017)
This study aims to determine the effect of the independence, auditor ethics, competence, and auditing standards on audit quality in Public Accounting Firm in Central Java and Yogyakarta. This study used primary data in the form of questionnaire has been given to the auditor's as the respondents. This study also used secondary data from a complete list of Public Accounting Firm in Central Java and Yogyakarta. This study used purposive sampling method with the criteria of auditor's who are working in Public Accounting Firm in Central Java and Yogyakarta and the auditor's who has audited at least 1 year. From 70 questionnaires which had been distributed in 14 Public Accounting Firm in Central Java and Yogyakarta, only 60 questionnaires that can meet the criteria. This study used multiple regression analysis to test F, hypothesis test (t test), and the coefficient determination (R2). This study showed that independence does not affect on audit quality, and auditor ethics also do not affect on audit quality. This indicates that the independence and auditor ethics do not affect the good or the bad audit quality is produced by the auditor's. While competence effect on audit quality and auditing standards also affect on audit quality. This showed that the competence and auditing standards can affect the good quality or the bad quality on audit quality was produced by the auditor's in Public Accounting Firm Central Java and Yogyakarta.